INTEGRATED APPROACH TO THE CREATION OF ARTIFICIAL SUPPORT FOR ORTHOPEDIC STRUCTURES USING DENTAL IMPLANTS FOR DEFECTS OF THE DENTITION (Intent Research Scientific Journal, 2023)
The combination of different types of dental implants to support orthopedic fixed restorations is an effective way to restore masticatory function, no less effective than the traditional method of using two-stage screw implants as supports for fixed bridges.